Peran Struktur Modal, Kebijakan Dividen dan Kepemilikan Manajerial dalam Meningkatkan Manajemen Laba - Karuniawati, Yuli; Purwatiningsih, Purwatiningsih (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to determine and empirically prove the influence of capital structure, dividend policy and managerial ownership on earnings management (empirical study of energy companies listed on the Indonesian Stock Exchange for the 2018-2022 period). The data analysis used is panel data regression analysis with the help of a Windows-based econometric views computer program (Eviews version 12) to obtain a comprehensive picture of the relationship between one variable and another. Sampling was carried out using a purposive sampling technique so that the samples selected were based on criteria and outlier data of 10 (ten) companies. The research results show that simultaneously capital structure, dividend policy and managerial ownership influence earnings management. Partially, capital structure has an effect on earnings management, dividend policy has no effect on earnings management, and managerial ownership has no effect on earnings management.